VARIABEL-VARIABEL YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT DENGAN PARAGRAF GOING CONCERN - HARYO SUPARMUN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this study is to analyze the effect of bankruptcy prediction, firm growth, leverage, auditor reputation, quick ratio, return on assets on the receiving of an unqualified opinion with paragraph going concern. The samples in this study are manufacturing company listed in Indonesia Stock Exchange for period 2007 until 2011. 24 samples are obtained by purposive sampling method. This study uses binary logistic regression method to data analyzes. The results show that bankruptcy prediction, leverage and auditor reputation have influence to the receiving of an unqualified opinion with paragraph going concern. While, firm growth, quick ratio and return on assets do not have influence to unqualified opinion with paragraph on going concern.